PENGARUH KONSUMSI TELUR PUYUH TERHADAP KADAR HEMOGLOBIN DAN KOLESTEROL PADA REMAJA UMUR 13-15 TAHUN - Ika Purnama Sari; Listyaning Eko Martanti; Sri Sumarni (Jurnal Vokasi Kesehatan, 2020)
Iron deficiency anemia is a decreasing number of red blood cells in the blood caused by too little iron in the blood system, especially for the adolescents. To increase the hemoglobin levels can be done by consuming lots of foods that contain a high protein and iron. Quail eggs have a higher protein and iron content among other eggs. The purpose of this study is to determine the different effect of the consumption of quail eggs to the hemoglobin and cholesterol levels in the adolescents. This study uses true experiment with pretest-posttest design with the control group. The population is a group of girl students aged 13-15 years old who was menstruating at SMP Al Munawir Gringsing, Batang district. The sampling technique used is simple random sampling. The hemoglobin and cholesterol levels were measured when the respondents were menstruating on the first day and the sixth day. The intervention group was given the quail eggs for 5 days during the menstruation and the control group was only observed. The results of the dependent t test hemoglobin level p-value intervention group 0,000 and p-value control group 0,000, and cholesterol p-value intervention group 0,012 and control group p-value 0,003, so it can be concluded that there is an effect of quail eggs consumption on the hemoglobin and cholesterol levels. The results of the independent test of the difference in hemoglobin p-value 0.001 and the difference in the level of cholesterol p-value of 0.002, so it can be concluded that there is a significant difference in the consumption of the quail eggs on the hemoglobin and cholesterol levels. It is expected that the consumption of the quail eggs for the adolescents can be given as a daily menu in order to increase the hemoglobin levels.